Answer:
0.06x + 0.15y = 69.84
x = (69.84 - 0.15y) / 0.06
y = (69.84 - 0.06x) / 0.15
x + y = 852
((69.84 - 0.15y) / 0.06) + y = 852
y = ?
(I'm not trying to give you the answer but guide you how to do it)
Answer:
A. -12h² - 22h + 14
Step-by-step explanation:
(-4h +2)(3h +7) = -4h(3h +7) +2(3h +7) . . . . . . . (a +b)c = ac +bc
= (-4h)(3h) + (-4h)(7) + (2)(3h) + (2)(7) . . . . . . . a(b +c) = ab +ac . . . (twice)
= -12h² -28h +6h +14
= -12h² -22h +14 . . . . . . . . collect terms
Answer:
38 mpg
Step-by-step explanation:
Initial efficiency = 39 mpg
Initial speed = 40 mph
Final speed = 50 mph
The efficiency drop between 40 mph and 50 mph is given by:
![E_d = 0.1 \frac{mpg}{mph}*\Delta V](https://tex.z-dn.net/?f=E_d%20%3D%200.1%20%5Cfrac%7Bmpg%7D%7Bmph%7D%2A%5CDelta%20V)
The total efficiency drop from 40 to 50 mph is:
![E_d = 0.1 \frac{mpg}{mph}*(50-40)mph\\E_d = 1\ mpg](https://tex.z-dn.net/?f=E_d%20%3D%200.1%20%5Cfrac%7Bmpg%7D%7Bmph%7D%2A%2850-40%29mph%5C%5CE_d%20%3D%201%5C%20mpg)
Therefore, the efficiency at 50 mph is:
![E_{50} = E_{40} -E_d\\E_{50} = 39 -1\\E_{50} = 38\ mpg](https://tex.z-dn.net/?f=E_%7B50%7D%20%3D%20E_%7B40%7D%20-E_d%5C%5CE_%7B50%7D%20%3D%2039%20-1%5C%5CE_%7B50%7D%20%3D%2038%5C%20mpg)
Answer:
x=9
Step-by-step explanation:
√117²=x²+6²
117=x²+36
x²=117-36
x²=81
x=9